Renal Cystic Nephroma, a Diagnostic Challenge and Dilemma since 19th Century, A Literature Review - M, Darouichi (Archives of Clinical and Biomedical Research, 2019)
Kidney cystic nephroma is a rare tumor with a prevalence of less than 1% and predominant in adult women. This benign entity still poses real preoperative diagnostic problems when comparing to cystic renal cell carcinoma. Indeed, despite advances in medical imaging, there still is a lack of specificity of radiological signs and surgical exploration is necessary for diagnosis. Here, we report an interesting case in a 53-year-old woman. Sonography, abdominal CT scan and MRI suspected a cystic renal malignant tumor, leading to a right radical nephrectomy. The diagnosis of cystic nephroma was finally made by histological and immunohistochemically staining. We will discuss this case that precisely illustrates the diagnostic dilemma regarding this disease. We will then discuss the Physio-pathological, immunohistochemical and radiological aspects of this rare entity of uncertain etiology with a review of the literature.